Early development of ubiquitous acanthocytosis and extravascular hemolysis in lung cancer patients receiving alectinib - Kunz, Julia; Wiedemann, Christiane R.; Grosch, Heidrun; Kriegsmann, Katharina; Gryzik, Stefanie; Felden, Julia; Hundemer, Michael; Şeker-Cin, Huriye; Stenzinger, Miriam; Leo, Albrecht; Stenzinger, Albrecht; Thomas, Michael; et al. (Cancers, 2022)
Alectinib is a standard initial treatment for patients with advanced anaplastic lymphoma kinase (ALK) rearranged non-small-cell lung cancer (NSCLC). The current study analyzed a prospective cohort of 24 consecutive alectinib-treated patients and controls in order to comprehensively characterize longitudinal erythrocyte changes under treatment with ALK inhibitors. Upon starting alectinib, all examined patients developed reticulocytosis and abnormal erythrocyte morphology with anisocytosis and a predominance of acanthocytes (64% of red blood cells on average, range 36-100%) in the peripheral blood smear within approximately 2 weeks. Changes were accompanied by a gradual reduction in Eosin-5-maleimide (EMA) binding, which became pathologic (<80% of cells) within 1-2 months in all cases, mimicking an abortive form of hereditary spherocytosis. The latter could be ruled out in 3/3 of analyzed cases by normal sequencing results for the ANK1, EPB42, SLC4A1, SPTA1, or SBTB genes. The direct Coombs test was also negative in 11/11 tested cases. Besides, anemia, increased LDH, and increased bilirubin were noted in a fraction of patients only, ranging between 42 and 68%. Furthermore, haptoglobin decreases were infrequent, occurring in approximately 1/3 of cases only, and mild, with an average value of 0.93 g/L within the normal range of 0.3-2 g/dL, suggesting that hemolysis occurred predominantly in the extravascular compartment, likely due to splenic trapping of the deformed erythrocytes. These changes showed no association with progression-free survival under alectinib or molecular features, i.e., ALK fusion variant or TP53 status of the disease, and resolved upon a switch to an alternative ALK inhibitor. Thus, alectinib induces mild, reversible erythrocyte changes in practically all treated patients, whose most sensitive signs are aberrant red cell morphology in the peripheral smear, a pathologic EMA test, and reactive reticulocytosis. Frank hemolytic anemia is rare, but mild subclinical hemolysis is very frequent and poses differential-diagnostic problems. Alectinib can be continued under the regular control of hemolysis parameters, but the risk of long-term complications, such as cholelithiasis due to increased serum bilirubin in most patients, remains unclear at present.
Gesehen am 14.07.2022